2005
DOI: 10.1117/12.596921
|View full text |Cite
|
Sign up to set email alerts
|

Silicon photonics: the early years

Abstract: The purpose of this paper is to set the scene for what promises to be an outstanding conference. To this end the paper will survey the early work in silicon photonics from the late 1980s to the mid 1990s. This was when the more fundamental studies of basic building blocks were carried out, such as study of the silicon optical waveguide itself, the contributions to loss and improvement of waveguiding devices. Issues such as how to achieve modulation, and how to implement a modulator, the criteria for single mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 109 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…In the late 1980s and early 1990s, Separation by IMplantated OXygen (SIMOX) and Bond and the Etchback SOI (BESOI) techniques were the two main methods for SOI wafer fabrication [22], [33]- [39]. Initially, very large propagation losses (∼30 dB/cm) from a 2-μm-thick planar waveguide [37] were demonstrated in these wafers.…”
Section: W a V E G U I D E A N D Pa S S I V E C O M P O N E N T Smentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1980s and early 1990s, Separation by IMplantated OXygen (SIMOX) and Bond and the Etchback SOI (BESOI) techniques were the two main methods for SOI wafer fabrication [22], [33]- [39]. Initially, very large propagation losses (∼30 dB/cm) from a 2-μm-thick planar waveguide [37] were demonstrated in these wafers.…”
Section: W a V E G U I D E A N D Pa S S I V E C O M P O N E N T Smentioning
confidence: 99%
“…Around 1989, Kurdi et al [31] and Davis et al [33] reduced propagation losses to acceptable levels achieving 4 and 1 dB/cm, respectively. Multiplelayer waveguiding structures using SIMOX fabrication technology were also demonstrated [22], [32], [35]. During the1990s, most of the attention was turned to rib waveguides, structures that could confine light in both dimensions.…”
Section: W a V E G U I D E A N D Pa S S I V E C O M P O N E N T Smentioning
confidence: 99%
“…Silicon photonics is accepted as the next-generation com-photonics-high data densities and transmission over longer distances. One potential application was of waveguides in silicon-on-insulator (SOI) wafer structures in 1985 [5,6], which was commercialized later in 1989 by Bookham Technology Ltd. [7].…”
Section: Silicon Photonics: a Brief Overviewmentioning
confidence: 99%
“…Rickman et al confirmed that the propagation loss was not going to be a serious issue in the development of the SOI technology [30]. The earliest SOI planar waveguides were rib waveguides with multi-micron width [31].…”
Section: Soi Platformmentioning
confidence: 99%